ҚАРАҚАЛПАҚ ХАЛҚЫНДАҒЫ ЫРЫМ ХӘМ ТЫЙЫМ СӨЗЛЕРДИҢ ТӘРБИЯЛЫҚ ӘҲМИЙЕТИ - Исмайлов, А.С. (SCIENCE and SOCIETY, 2018)
The article deals with the traditions and customs of our people. On the way to achieve the goal, our teenagers can get information about the issues of assessing cultural heritage, propagating old traditions and rites, the importance of superstition and forbidden words in the spiritual and aesthetic education of people.
Keywords: traditions; rituals; superstition; national education; ethics; aesthetics; spirituality; covenants